A class of transition metal-oxide@MnOx core–shell structured oxygen electrocatalysts for reversible O2 reduction and evolution reactions. Issue 36 (29th August 2016) - Cheng, Yi; Dou, Shuo; Saunders, Martin; Zhang, Jin; Pan, Jian; Wang, Shuangyin; Jiang, San Ping
Abstract : A novel metal-oxide@MnO x core–shell type structured electrocatalyst has been developed with an excellent bifunctional activity for the ORR and OER and good durability. Abstract : It is highly desirable but challenging to develop a highly active as well as durable bifunctional electrocatalyst for the reversible oxygen reduction reaction and evolution reaction (ORR & OER). Here a new class of bifunctional oxygen electrocatalysts has been developed based on ultrafine transition metal-oxide nanoparticles (NPs), such as NiO, FeO or NiFeO, embedded in an amorphous MnO x shell, where the embedded NP core contributes to the high OER activity and the porous amorphous MnO x shell functions as an effective ORR catalyst as well as providing effective structural confinement to the metal-oxide NP core. The best performance was obtained for NiFeO@MnO x, exhibiting a potential gap, Δ E, of 0.798 V to achieve a current of 3 mA cm −2 for the ORR and 5 mA cm −2 for the OER in 0.1 M KOH solution, better than that of Ir/C (0.924 V) and Pt/C (1.031 V). Most importantly, NiFeO@MnO x shows superior stability due to the outstanding structural confinement effect of the amorphous MnO x, achieving a Δ E of 0.881 V after 300 cycles, outperforming 1.093 V obtained for the state-of-the-art Ir–Pt/C oxygen electrocatalysts.